Adolescence- ‘The Period of Storm and Stress’: A Systematic Review of the Significant Social Experiences Contributing to Deterioration in Adolescent Mental Health - Rajannya Mukherjee, (International Journal of Scientific Research in Science and Technology, 2025)
Mental health refers to an individual’s adjustment with a maximal effectiveness, satisfaction, happiness and socially considerate behaviour and the ability to face and accept the reality of life. The present research is a review of several important aspects of mental health in adolescents. Significant stressors that lead to mental health issues in adolescents as reviewed were- academic pressure, peer bullying, dysfunctional family relations, tumultuous platonic and romantic relationships and body image issues. Interventions in schools and communities implement strategies that foster supportive interactions among diverse resource persons including teachers, parents, community members, and other professionals. The effects of the mental health interventions reported on adolescents' problems include a decrease in disruptive behaviours and affective symptoms such as depression and anxiety and an increase in the positive affect and emotional regulation skills in adolescents. Whereas, interactions among different resource persons seem to be a relevant aspect across the interventions, more research is needed to conclude its effect on the outcomes of the studies reviewed with an increase in social skills, as well as an improvement in personal well-being.
Keywords: Adolescence; anxiety; depression; dysfunctional family; peer bullying; academic pressure; body shaming